One Parameter Deformation of Symmetric Toda Lattice Hierarchy (Communications in Mathematical Research, 2020)
In this paper, we study one parameter deformation of full symmetric Todahierarchy. This deformation is induced by Hom-Lie algebras, or is the applications ofHom-Lie algebras. We mainly consider three kinds of deformations, and give solutionsto deformations respectively under some conditions.
Keywords: Hom-Lie algebra; deformation; symmetric Toda hierrchy